Characteristics of Low Back Pain in Pregnancy, Risk Factors, and Its Effects on Quality of Life - Berber, Münevver Aybüke; Satılmış, İlkay Güngör (Elsevier BV, 2020)
Low back pain is a common problem experienced during pregnancy, negatively affecting quality of life.The study aimed to determine the prevalence and risk factors of low back pain during pregnancy and its effects on the quality of life.This was a descriptive and cross-sectional study.Its setting was the Kastamonu State Hospital Obstetrics and Gynecology clinics.The study consisted of 400 pregnant women.The sample consisted of 400 pregnant women. Data were collected using an introductory information form, a back pain evaluation form, the Visual Analog Scale (VAS), and the Oswestry Disability Index (ODI).In terms of back pain, 75.3% of the participants experienced back pain during their current pregnancy. The mean VAS score for back pain during their current pregnancy was 4.91±1.88. Low back pain was generally experienced in the third trimester (85.5%) and in the lumbar area (45.5%). Factors associated with low back pain included income status, trimester, gestational weight gain, frequent urinary tract infections, a hunchback posture, having experienced low back pain during previous pregnancies, and a history of low back pain. The mean percentage score on the ODI, which assesses the effect of low back pain on functional status, was 31.87% ± 15.56%, and for the majority of the participants (45.7%), low back pain was found to slightly limit their activities of daily living.The prevalence of low back pain in pregnancy is quite high, and low back pain slightly limits women's activities of daily living.
Keywords: Adult; Visual Analog Scale; Pregnancy Complications; Cross-Sectional Studies; Pregnancy; Risk Factors; Surveys and Questionnaires; Quality of Life; Humans; Female; Low Back Pain; Pain Measurement; 3. Good health